2017
DOI: 10.1590/s0100-83582017350100005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mechanism Responsible for the Low-Level Resistance to Glyphosate in Goosegrass

Abstract: -Goosegrass (Eleusine indica) infests various crops, being reported as low-level resistant (LLR) to glyphosate. The objectives of this study were to evaluate the mechanisms of resistance to glyphosate in goosegrass by the cyt-P450 complex to identify changes in leaf anatomy of these plants and quantify the accumulation of shikimate in biotypes susceptible and with LLR. The metabolic rate was assessed by applying the cyt-P450 malathion inhibitor 30 minutes before the herbicide application. The analysis of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…2003) in weed species like Galinsoga parviflora, Conyza bonaeriensis and Ipomoea cairica, considered a potential barrier to penetration of herbicides applied to the canopy, the low stomatal densities in the adaxial side, that were of (48, 42 and 47 stomata mm -2 ) in the adaxial side and of (156, 162 and 143 stomata mm -2 ) in the abaxial side. Ulguin et al (2017), in studies on Eleusine indica, found that characteristics of surface and leaf anatomy may affect the effectiveness of glyphosate absorption by weeds. Features such as composition of the cuticle, number of stomata, and trichomes interfere with the foliar absorption of herbicides and may indicate auxiliary resistance Thus, weeds anatomy characteristics may influence resistance to herbicides, and therefore their determination is important.…”
Section: A Epidermic Variablesmentioning
confidence: 99%
“…2003) in weed species like Galinsoga parviflora, Conyza bonaeriensis and Ipomoea cairica, considered a potential barrier to penetration of herbicides applied to the canopy, the low stomatal densities in the adaxial side, that were of (48, 42 and 47 stomata mm -2 ) in the adaxial side and of (156, 162 and 143 stomata mm -2 ) in the abaxial side. Ulguin et al (2017), in studies on Eleusine indica, found that characteristics of surface and leaf anatomy may affect the effectiveness of glyphosate absorption by weeds. Features such as composition of the cuticle, number of stomata, and trichomes interfere with the foliar absorption of herbicides and may indicate auxiliary resistance Thus, weeds anatomy characteristics may influence resistance to herbicides, and therefore their determination is important.…”
Section: A Epidermic Variablesmentioning
confidence: 99%
“…Comparative analysis of the effects of complex stress and single stress on CF parameters of two weeds Compared with single stress, compound stress not only disrupted the physiological pattern of weeds but also directly damaged the leaf structure of weeds, broke the obstruction of weed cuticle layer, made glufosinate enter into weeds faster, and combined with ATP and occupied the reaction site of GS, the synthesis of GS was blocked, and photosynthesis was affected, which made the weeds die much more efficiently (Ulguim et al, 2019;Takano et al, 2020a;Takano et al, 2020b). It is evident from the time that the composite stress leads to the death of the weed in a far shorter time than when a single stress acts on the weed.…”
Section: Comparative Analysis Of the Effects Of Mechanical And Chemic...mentioning
confidence: 99%
“…2003) in weed species like Galinsoga parviflora, Conyza bonaeriensis and Ipomoea cairica, considered a potential barrier to penetration of herbicides applied to the canopy, the low stomatal densities in the adaxial side, that were of (48, 42 and 47 stomata mm -2 ) in the adaxial side and of (156, 162 and 143 stomata mm -2 ) in the abaxial side. Ulguin et al (2017), in studies on Eleusine indica, found that characteristics of surface and leaf anatomy may affect the effectiveness of glyphosate absorption by weeds. Features such as composition of the cuticle, number of stomata, and trichomes interfere with the foliar absorption of herbicides and may indicate auxiliary resistance mechanisms.…”
Section: A -Epidermic Variablesmentioning
confidence: 99%